Devil's advocate [videorecording (DVD)] - Reeves, Keanu; Pacino, Al, 1940-; Theron, Charlize; Hackford, Taylor, 1944-; Neiderman, Andrew (Warner Home Video, 1998)
Hotshot attorney Kevin Lomax's 64-0 case record has brought him a tempting offer from an elite New York firm. But the job Lomax accepts isn't what it seems. The Devil is in the details.